AgNPs biosynthesized from Pseudomonas Z9.3 metabolites as antimicrobial agents against bacterial and fungal pathogens - Plokhovska, Svitlana; Fuente-González, Elena; Gutierrez-Albanchez, Enrique; Gutierrez-Mañero, Francisco Javier; Ramos-Solano, Beatriz (Frontiers in Microbiology, 2025)
IntroductionAn eco-friendly method for the biosynthesis of functional silver nanoparticles (AgNPs) using plant growth-promoting bacteria (PGPB), specifically Pseudomonas sp. Z9.3, has been developed. The growing need for sustainable and non-toxic nanoparticle production makes this method significant for various applications.MethodsThe influence of physicochemical parameters, such as temperature, pH, and concentrations of AgNO3, on the synthesis of AgNPs was studied. The formation of AgNPs was confirmed by UVvis, SEM/TEM, FTIR, and XRD analysis. Antibacterial activity was assessed using the antibacterial disk diffusion assay. For antifungal activity, AgNPs were added to the agar medium, and the size of the inhibition zone was measured.Results and discussionTwo optimal conditions were identified: 37°C, pH 9, and a 5:1 ratio of bacterial supernatant to 5 mM AgNO3 (S1-9), and 37°C, pH 7, with a 2:4 ratio (S4-7). The UV-visible spectroscopy results showed an absorption range between 400 and 450 nm, confirming the formation of AgNPs. The SEM and TEM analysis showed the spherical shape of AgNPs with a good distribution of nanoparticles and the average size ranged from 8.24 ± 0.26 to 13.32 ± 0.4 nm. Antibacterial activity against different pathogenic bacteria and fungi was tested. Antibacterial activity of AgNPs against six human pathogens and three phytopathogens was evaluated. The antibacterial potential of S1-9 against Gram-negative strains was lower than against Gram-positive strains; in particular, S. epidermidis was the most sensitive (93.76%) compared to the equivalent concentration of Ag. In the case of fungi, S4-7 exhibited better inhibitory activity compared to the negative control. The highest dose (120 ppm) of S4-7 AgNP inhibited fungal growth being the most sensitive Alternaria sp. (74.97%), followed by Stemphylium sp. (66.30%), Fusarium sp. (45.62%), and Rhizopus sp. (32.68%). These findings highlight the potential of synthesized AgNPs as antimicrobial agents for both bacterial and fungal pathogens.